Counseling on Processing of Waste into Solid Organic Fertilizer for GAPOKTAN Farmers Rukun Tani Segobang Village, Licin District, Banyuwangi Regency, East Java - Tanti Kustiari; Ujang Suryadi; Ikomatun Nadipah (Peneliti Teknologi Teknik Indonesia, 2022)
Cattle and sheep waste contain chemical elements that are beneficial to the environment. Livestock waste which is processed into fertilizer is very useful for the fertility of agricultural land. The processed livestock waste is organic compost or known as manure. Farmers generally use compost to improve soil productivity, so livestock processing businesses have good prospects as an alternative to providing fertilizer other than chemical fertilizers. Farmers in Segobang village have several livestock. The problem is that the waste is not treated and has polluted the environment. Farmers generally have limitations in disposing of livestock waste or manure. In community service activities, trying to introduce ways to use livestock waste to be processed into organic fertilizer. The goal is that it can be used by farmers to fertilize the soil and can reduce input costs for farmers. Community empowerment programs, namely facilitation and counseling for farmers, breeders members of Gapoktan Rukun Tani with animal waste processing materials, the process of making solid organic fertilizers, the urgency of using organic fertilizers, reducing the use of chemical fertilizers. The activity method begins with problem identification, prioritization and problem solving. This activity shows that there is an increase in knowledge, insight, awareness and skills of farmers processing waste into solid organic fertilizer, as well as increasing the use of organic fertilizer for paddy fields and plantations. Involvement requires farmers, Gapoktan officials in collecting waste, fermentation routines every week so they can produce organic fertilizer at 2 tons per 2 weeks. The users of organic fertilizers extend from members of the combined farmer groups to the general public. The success of the Gapoktan farmer institutional unit in organic fertilizer production was able to reduce input costs. This attracted the interest of various other farmer groups to adopt. The program for processing waste into organic fertilizer can provide benefits for increasing the economy, agricultural productivity, the environment and the formation of a new livestock waste processing business unit.